Creating Breastfeeding friendly environments : implementation of model policies and practices in the Birthing facility - Page-Goertz, Sallie; McCamman, Sarah (Sudbury, MA : Jones and Barlett, 1996)
This module presents policies and practices needed for getting breastfeeding off to best start. Examine the research behind each recommendation. Learn strategies for policy implementation
Best Beginnings Productions
System Requirements : 486 (pentium recommended), 8 MB RAM, 4x CD-ROm drive, QuickTime for windows 2.1.1
System Requirements : Macintosh : 68030 ('040 or PowerMac recommended), 8 MB RAM, 2 x CD-ROM Drive (4x speed or higher recommended, QuickTime for windows 2.1.1
Keywords: Breast feeding; Infant nutrition